2013
DOI: 10.2741/4110
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance and targeting of HER family in colorectal cancer 

Abstract: Colorectal cancer is one of the leading causes of cancer deaths. At present, anti-epidermal growth factor receptor (EGFR) monoclonal antibodies (mAbs) cetuximab and panitumumab and anti-vascular endothelial growth factor (VEGF) mAb bevacizumab have been incorporated into treatment paradigms for patients with refractory metastatic colorectal cancer. However, many patients simply do not respond to these treatments or eventually acquire resistance following a short course therapy. In this article, we review the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 133 publications
(183 reference statements)
1
31
0
Order By: Relevance
“…Several studies have examined the mRNA expression levels of EGFR ligands and have found an association between the expression level of epiregulin, amphiregulin and TGFα and response to treatment with cetuximab [3, 18, 19, 24, 44, 45]. However, the increased expressed level of these genes may not always be translated into the corresponding proteins, which are directly competing with antibodies to bind on the EGFR on tumour cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have examined the mRNA expression levels of EGFR ligands and have found an association between the expression level of epiregulin, amphiregulin and TGFα and response to treatment with cetuximab [3, 18, 19, 24, 44, 45]. However, the increased expressed level of these genes may not always be translated into the corresponding proteins, which are directly competing with antibodies to bind on the EGFR on tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, colorectal cancer is estimated to be the third most commonly diagnosed cancer (134,900) and the third leading cause of cancer deaths (49,190) in the USA [2], highlighting the need for developing more effective and less toxic therapeutic agents. In the last three decades, the aberrant expression of the epidermal growth factor receptor (EGFR) has been reported in a wide range of tumours including colorectal, head and neck and lung cancers and the EGFR is currently an important therapeutic target for targeted therapy with anti-EGFR antibodies in such patients [3]. While treatment with a combination of antibodies and cytotoxic drugs improves response rate and median time to progression in some colorectal cancer patients, the duration of response is often limited in most patients with an advanced stage of the disease [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They exhibit aberrant signal transduction in many types of solid human cancers, including non-small cell lung cancer (NSCLC), breast cancer (BC), bladder cancer, ovarian cancer, colorectal cancer, pancreatic cancer and head and neck squamous cell cancer (HNSCC) (Ciardiello and Tortora 2008; Ioannou et al 2012; Khelwatty et al 2013). This exaggerated signalling may involve an enhanced signal input due to increased exposure to ErbB ligands (Modjtahedi and Dean 1994; Zhang et al 2007).…”
Section: Introductionmentioning
confidence: 99%